2010
DOI: 10.1111/j.1574-695x.2010.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factor cytotoxin-associated gene A in Helicobacter pylori is downregulated by interferon-γin vitro

Abstract: Helicobacter pylori-infected gastric mucosa is characterized by high levels of interferon-γ (IFN-γ), but whether the high level of IFN-γ regulates the virulence of H. pylori is unclear. Here, we characterized the response of H. pylori to IFN-γ and found by indirect immunofluorescence that IFN-γ can bind to H. pylori. The binding resulted in the altered expression of 14 proteins, including the virulence factor, cytotoxin-associated gene A (CagA), whose expression was downregulated. The transcription and transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…Consistent with these findings, Sayi et al (48) further demonstrated the tumorigenic risk caused by IFN-g, although IFN-g also triggers clearance during H. pylori infection. For antimicrobial activity, in addition to activating macrophages for phagocytosis, CagA protein is inhibited by IFN-g through an asyet-unknown mechanism, as reported previously (28). To demonstrate the antimicrobial effect of IFN-g, we confirmed that pretreatment with IFN-g decreased CagA expression, as detected by Western blot analysis (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with these findings, Sayi et al (48) further demonstrated the tumorigenic risk caused by IFN-g, although IFN-g also triggers clearance during H. pylori infection. For antimicrobial activity, in addition to activating macrophages for phagocytosis, CagA protein is inhibited by IFN-g through an asyet-unknown mechanism, as reported previously (28). To demonstrate the antimicrobial effect of IFN-g, we confirmed that pretreatment with IFN-g decreased CagA expression, as detected by Western blot analysis (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, polymorphisms in IFNGRs affect H. pylori infection in human (27). IFN-g also confers antimicrobial activity directly against CagA expression in H. pylori infection (28) and prevents gastric carcinogenesis by inducing epithelial cell autophagy and T cell apoptosis (29). However, H. pylori may disrupt IFN-g signaling through an unknown mechanism (30).…”
mentioning
confidence: 99%
“…However, H. pylori can disrupt STAT1-mediated IFN- γ -induced signal transduction in epithelial cells [ 20 ]. Moreover, when H. pylori is exposed to IFN- γ ; the main virulence factor cytotoxin-associated gene A (CagA) is downregulated [ 21 ], which is beneficial for persistent colonization [ 22 ]. Thus, H. pylori may actively respond to altered IFN- γ levels for persistent colonization.…”
Section: Introductionmentioning
confidence: 99%
“…10 IFN-␥ plays a dual role in response to H. pylori infection; on the one hand, it induces gastric inflammation and promotes the appearance of pre-neoplastic lesions caused by the infection, and on the other, IFN-␥ reduces bacterial colonization and is essential for the elimination of the infection. [11][12] Previous studies found that IFN-␥ levels were higher in patients infected with H. pylori than in uninfected patients. 9,[13][14][15] In 2007, Wang et al found that in patients infected with cagA + H. pylori, the cellular immune response mediated by Th1 cells was associated with earlier stages of gastric carcinogenesis, whereas humoral immunity mediated by Th2 cells predominated in the advanced stages.…”
Section: Introductionmentioning
confidence: 99%